Implementasi Supervisi Pendidikan dalam Meningkatkan Kredibilitas Tenaga Pendidik Melalui Pendekatan Directiv, Non Directiv dan Kolaboratif - Maizah, St.; Abidin, Zeinal; Inayati, Mahfida (Medan Resource Center, 2023)
Supervision plays a crucial role in maintaining and improving educational resources. Competent supervisors are equipped with theoretical knowledge and practical understanding to effectively address challenges and contribute to the progress of educational institutions. They provide solutions and support to teachers and staff through directive, non-directive, and collaborative approaches. Effective supervision requires a deep understanding of the issues at hand. It is not limited to criticism but serves as a platform for problem-solving. Continuous coaching is essential for teachers and staff, ensuring their professional growth and development. A well-structured system is vital for supervisors to fulfill their responsibilities. Overall, supervision serves as a valuable mechanism for enhancing educational institutions and nurturing a conducive learning environment.